Pathogenicity test of Sclerotium rolfsii isolates causing foot and root rot disease of betelvine (Piper betle L.) - Md. Hafizur Rahman; Md. Rafiqul Islam; F. M. Aminuzzaman; Kallol Das; M. M. A. Patwary; M. Z. Masud (Turkish Journal of Agriculture: Food Science and Technology)
The experiment was conducted under in-vivo condition in a betelvine baroj at Sher-e-Bangla Agricultural University (SAU), Dhaka-1207, Bangladesh. Nineteen isolates of Sclerotium rolfsii collected from different regions of Bangladesh designated as isolate-1 to isolate-19. Soil inoculated with S. rolfsii exhibited mycelial growth on the soil surface and around the base of the betelvine plant within 2-4 days after inoculation. Only 2 days after inoculation were required to manifest cottony colony on soil surface near root zone of inoculated betelvine plants by the isolate-3, 5, 7, 9 and 12. The first disease symptoms were observed within 6 to 16 days after inoculation where minimum days were required by the isolate-9 and maximum by the isolate-2 and 14. The highest lesion length (6.50 cm) was produced by the isolate-9 and isolate-13. All the isolates were found to be pathogenic in some cases, disease delayed due to their degree of pathogenicity. The isolate-9 showed highest disease incidence of 100% which was superior as compared to all other isolates at 15 days after inoculation. The isolate-19 showed least disease incidence of 66.66% even at 30 days after inoculation. Among the isolates, the most pathogenic one was isolate-9 collected from Kaligonj upazilla of Jhenaidah.